March's advanced organic chemistry : reactions, mechanisms, and structure. - Smith, Michael, 1946 October 17- (John Wiley & Sons, Inc., 2020)
"The revised and updated 8th edition of March's Advanced Organic Chemistry explains the theories and examples of organic chemistry, providing the most comprehensive resource about organic chemistry available. Readers are guided on planning and execution of multi-step synthetic reactions, with detailed descriptions of all the reactions. The opening chapters deal with the structure of organic compounds and discuss important organic chemistry bonds, fundamental principles of conformation, and stereochemistry of organic molecules, and reactive intermediates in organic chemistry. Further coverage concerns general principles of mechanism in organic chemistry, including acids and bases, photochemistry, sonochemistry and microwave irradiation, and finally the relationship between structure and reactivity. The final chapters cover the nature and the scope of organic reactions and their mechanisms. The 8th Edition proves again it is a must-have desktop reference and textbook for every student and professional working in organic chemistry or related fields"-- Provided by publisher.
Keywords: Chemistry, Organic.; elektronické knihy; electronic books